THE SIGNIFICANCE OF THE FINANCIAL SERVICES AUTHORITY’S APPROVAL ON THE SALE AND PURCHASE OF A LIMITED LIABILITY RURAL BANK’S SHARES - Novyanti Indah; Dhoni Martin (International Journal on Orange Technologies, 2021)
This thesis will discuss the process of buying and selling shares of Rural Banks in the form of Limited Liability Companies According to applicable regulations and the significant of the Financial Services Authority’s approval on the sale and purchase of shares of Rural Banks. The author uses the theory of law as a grand theory, banking law theory as a middle theory and certainty of law as applied theory in this thesis. The research method used is normative juridical supported by empirical, namely by examining the rules relating to the sale and purchase of shares of Rural Banks and field research in the form of interviews conducted at the Financial Services Authority